Women’s sexuality, embodiment and evangelicalism - Payne, Melissa (Theology & sexuality, 2023)
For centuries, the Christian God has been depicted through a predominantly masculine framework that has left women devoid of relating to the Divine in her woman-ness. Women's sexuality within the Canadian Evangelical context remains a topic that is often not discussed. This study looks at the convergence of three areas of human experience: sexuality, embodiment, and religious/spiritual experience within this specific church context. It looks on how women have experienced this religious phenomenon and the impact on the self as sexual and embodied beings. Data analysis revealed five emergent themes: (1) shame around the female body and sexual experience, (2) dialogue around the female body, (3) disintegration and disembodiment, (4) sources of Identity and (5) evolving views of Spirituality and Sexuality. To stay withing the journal's guidelines on text volume, the current article focuses on the first three themes.